A facile soft-template synthesis of mesoporous polymeric and carbonaceous nanospheres - Liu, Jian; Yang, T.; Wang, D.; Lu, G.; Zhao, D.; Qiao, S. (Macmillan Publishers Limited, 2013)
Owing to the weak self-assembly ability of precursor components and the serious crosslinking of neighbouring nanospheres during a hydrothermal process, the synthesis of monodisperse mesoporous polymer nanospheres with diameters below 500 nm remains a great challenge. Here we extend the synthesis method of mesoporous silica nanospheres to enable the preparation of ordered mesoporous resorcinol formaldehyde nanospheres with particle size from 80 to 400 nm and mesopores of ~3.5 nm in diameter. By finely tuning the synthesis parameters, multi-layered mesoporous resorcinol formaldehyde hollow nanospheres can be successfully synthesized. Mesoporous carbon nanospheres and hollow nanospheres with high surface area are further obtained through carbonization of the polymer spheres. The resulting mesoporous carbon nanospheres are demonstrated as the host cathode material for lithium–sulphur batteries. The synthesis strategy provides a benchmark for fabricating well-defined porous carbonaceous nanospheres with potential for energy storage and conversion applications.